Analysis of male Leptagrion Selys, 1876 sensu lato (Odonata: Coenagrionidae) with description of four new genera and a new species - Lencioni, F.a.a. (Zootaxa, 2022)
The species currently included in Leptagrion Selys, 1876 are found to belong in five different genera: Leptagrion sensu stricto, including the type species Leptagrion macrurum (Burmeister, 1839), two previously described species, viz, Leptagrion bocainense Santos, 1979 and Leptagrion auriceps St. Quentin, 1960 (here recovered from synonym), and Leptagrion vilelai sp. nov.; Fredyagrion gen. nov. to include Leptagrion andromache Hagen in Selys, 1876, Leptagrion dispar Selys, 1876, Leptagrion elongatum Selys, 1876, Leptagrion aculeatum Santos, 1965a, Leptagrion capixabae Santos, 1965b, Leptagrion siqueirai Santos, 1968b, Leptagrion vriesianum Santos, 1978, Leptagrion afonsoi Machado, 2007, Leptagrion lencioninetoi Lencioni, 2017b, Leptagrion itabaiana Vilela et al., 2021a, and Leptagrion jeromei Lencioni, Vilela & Furieri, 2021 in Vilela et al., 2021b; Nathaliagrion gen. nov. to include Leptagrion porrectum Hagen in Selys, 1876 and Leptagrion perlongum Calvert, 1909; Machadagrion gen. nov. to include Leptagrion garbei Santos, 1961, Leptagrion dardanoi Santos, 1968a and Leptagrion cyanostigma Machado, 2012; Kiautagrion gen. nov. for and Leptagrion acutum Santos, 1961. Diagnostic illustrations of all species are presented.